Evolusi Teori Linguistik Dalam Tradisi Arab: Dari Al-Khalil Hingga Ibn Jinni - Nurfadillah; Sulkifli (Universitas Islam Negeri Alauddin, 2025)
This research aims to examine the evolution of classical Arabic linguistic theory from the 8th to 10th centuries CE by analyzing the contributions of three principal figures: al-Khalil ibn Ahmad, Sibawayh, and Ibn Jinni. Through historical-comparative approaches and textual analysis of fundamental works such as Kitab al-'Ayn, al-Kitab, and al-Khasa'is, this study traces the transformation of linguistic thought from phonological and morphological foundations, through syntactic systematization, to semantic-philosophical development. The research methodology involves in-depth philological examination of classical manuscripts and cross-period comparison to identify patterns of theoretical evolution. The findings reveal methodological continuity based on sima'i (auditory transmission) and qiyas (analogical reasoning) transmitted across generations, alongside conceptual innovations that enriched the theoretical dimensions of Arabic linguistics. These discoveries illuminate how each period presented distinctive contributions: al-Khalil with lexical-phonological systematization, Sibawayh with comprehensive grammatical codification, and Ibn Jinni with philosophical elaboration of language. This research confirms that the Arabic linguistic tradition is dynamic, receptive to intellectual development, and maintains significant relevance in contemporary linguistic discourse.